"Volunteers Are Not Paid Because They Are Priceless": Community Health Worker Capacities and Values in an AIDS Treatment Intervention in Urban Ethiopia. (24th September 2014) - Maes, Kenneth
Abstract : This article analyzes community health workers' (CHW) capacities for empathic service within an AIDS treatment program in Addis Ababa. I show how CHWs' capacities to build relationships with stigmatized people, reconcile family disputes, and confront death draw on a constellation of values, desires, and emotions encouraged by CHWs' families and religious teachings. I then examine the ways in which the capacities of CHWs were valued by the institutions that deployed them. NGO and government officials recognized that empathic care was crucial to both saving and improving the quality of people's lives. These institutional actors also defended a policy of not financially remunerating CHWs, partly by constructing their capacities as so valuable that they become "priceless" and therefore only remunerable with immaterial satisfaction. Positive change within CHW programs requires ethnographic analysis of how CHWs exercise capacities for empathic care as well as consideration of how global health institutions value these capacities.